IMPLEMENTATION OF DEMONSTRATION METHOD TO IMPROVE TEACHER KNOWLEDGE OF ADIWIYATA SCHOOL - Supriadi Supriadi (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
Preliminary observations made at SD Negeri 13 Kerinci Kanan Siak Regency, there was a phenomenon that some teachers did not know about environmentally sound schools, lack of knowledge of teachers and other school members regarding adiwiyata school policies, lack of implementation of adiwiyata schools, and so on. Based on the problems mentioned above, this school action research was carried out to increase teacher knowledge about Adiwiyata school and to find out the weaknesses and strengths of the implementation of demonstration methods to increase teacher knowledge in SD Negeri 13 Kerinci Kanan Siak Regency. This research was designed in the form of a School Action Research which was planned to be carried out in two cycles. The subjects of this study were the teachers at the SD Negeri 13 Kerinci Kanan Siak Regency, totalling 9 teachers. Based on the results of research conducted, Cycle I, no teacher has a percentage in the very good category while in the second cycle the percentage of teachers in the very good category is 33.3%. Good category, in the first cycle 44.4% increased to 55.5%, in the sufficient category, the first cycle gained a percentage of 33.3% and decreased to 11.2% in the second cycle. Whereas in the lack category, cycle I gained a percentage of 22.3% and in cycle II the percentage of teachers who were in the inadequate category was gone. Thus it can be concluded that the implementation of the demonstration method can increase teacher knowledge of adiwiyata schools in SD Negeri 13 Kerinci Kanan Siak Regency.